Mesh stiffness models for cylindrical gears: A detailed review - Marafona, João D.M.; Marques, Pedro M.T.; Martins, Ramiro C.; Seabra, Jorge H.O. (Mechanism and machine theory, 2021)
Gear transmissions have always been a subject of study for many different reasons which change due to the constant evolution of technology. Consequently, new topics must be addressed and different ways to solve the upcoming problems must be discovered. Gear mesh stiffness is a central topic for both gear design and gear dynamic modeling due to its ability to represent the gears’ behavior, making it a subject of high interest in the field of gear transmissions. Different types of models are used to establish the mesh stiffness of parallel axis cylindrical gears, namely, analytical, finite element, hybrid and approximated analytical models. Also, a dedicated section to mesh stiffness models for polymer gears is included. In this work, implementation guidelines for each class of model are presented along with relevant literature, providing a broad range of information in great detail. Lastly, the main conclusions for each type of model are discussed and an overview of the future evolution of gear mesh stiffness is given. •Review on gear mesh stiffness models.•Guidelines and implementation procedure for gear mesh stiffness models.•Gear transmission trends on gear mesh stiffness.